2016
DOI: 10.1103/physreve.94.043111
|View full text |Cite
|
Sign up to set email alerts
|

Lift force due to odd Hall viscosity

Abstract: We study the problem of flow of a neutral gas past an infinite cylinder at right angle to its axis at low Reynolds number when the fluid is characterized by broken time-reversal invariance, and hence by odd viscosity in addition to the normal even one. We solve the Oseen approximation to Navier-Stokes equation and calculate the lift force which appears due to the odd viscosity.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…5.1. Odd viscous flow past a sphere Two-dimensional flows past obstacles in the presence of a non-dissipative (odd) viscosity have previously been studied experimentally in Soni et al (2019) and theoretically in Kogan (2016). Lapa & Hughes (2014) also analysed the consequences on swimmers at low Reynolds numbers.…”
Section: Odd Viscous Flow Past An Obstaclementioning
confidence: 99%
See 1 more Smart Citation
“…5.1. Odd viscous flow past a sphere Two-dimensional flows past obstacles in the presence of a non-dissipative (odd) viscosity have previously been studied experimentally in Soni et al (2019) and theoretically in Kogan (2016). Lapa & Hughes (2014) also analysed the consequences on swimmers at low Reynolds numbers.…”
Section: Odd Viscous Flow Past An Obstaclementioning
confidence: 99%
“…In these two-dimensional cases, only the pressure field is modified by the additional viscous terms, while the velocity field remains unchanged. Nevertheless, Kogan (2016) reported that a lift force appears in the Oseen approximation (including inertia) of the flow past an infinite cylinder due to the non-dissipative viscosity. In this section, we consider three-dimensional flows.…”
Section: Odd Viscous Flow Past An Obstaclementioning
confidence: 99%
“…It is known that odd viscosity gives rise to anomalous hydrodynamic phenomena, such as robust surface waves at fluid boundaries [23,24] and an instability of a viscous film [25,26]. The hydrodynamic forces acting on various objects have also been studied in the presence of odd viscosity [27][28][29][30][31]. For a laterally moving rigid disk, the presence of a lift force was predicted within the Oseen approximation [27] or by considering a compressible 2D fluid [28].…”
Section: Introductionmentioning
confidence: 99%
“…The hydrodynamic forces acting on various objects have also been studied in the presence of odd viscosity [27][28][29][30][31]. For a laterally moving rigid disk, the presence of a lift force was predicted within the Oseen approximation [27] or by considering a compressible 2D fluid [28]. Moreover, odd viscosity is responsible for the torque acting on objects with time-varying area, such as an expanding bubble [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…To shed light on the generic low-energy properties of such quantum Hall states, we construct an effective action for systems with a semi-Dirac phase. Our construction contributes to the quest of understanding Hall viscosities; nondissipative transport coefficients that emerge in the context of topological order [21][22][23][24][25][26][27], fluid dynamics [28][29][30][31][32][33][34][35][36][37][38][39][40], or active matter [41][42][43][44][45][46]. Initially thought of as an elusive transport property, Hall viscosity has been experimentally identified in both hard [47] and soft [48] condensed matter experiments.…”
Section: Introductionmentioning
confidence: 99%